2008
DOI: 10.1093/jac/dkn486
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal mechanisms supporting boric acid therapy of Candida vaginitis

Abstract: Boric acid is fungistatic to fungicidal depending on concentration and temperature. Inhibition of oxidative metabolism appears to be a key antifungal mechanism, but inhibition of virulence probably contributes to therapeutic efficacy in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
77
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 16 publications
8
77
0
2
Order By: Relevance
“…The mechanism of action of BA against fungi is not yet understood, although some have suggested that it inhibits Candida filamentation [171]. Pointer et al have noted that the selective inhibitory effect of BA on C. albicans hyphae is likely be due to the disruption of apical cytoskeletal elements of growing hyphae [172].…”
Section: Boric Acidmentioning
confidence: 99%
“…The mechanism of action of BA against fungi is not yet understood, although some have suggested that it inhibits Candida filamentation [171]. Pointer et al have noted that the selective inhibitory effect of BA on C. albicans hyphae is likely be due to the disruption of apical cytoskeletal elements of growing hyphae [172].…”
Section: Boric Acidmentioning
confidence: 99%
“…Additionally, it is used as a pesticide and food preservative against plant fungicides (Turkoglu 2007). BA having antimicrobial activity (De Seta et al 2009), is able to strengthen the tissue antioxidant defenses via a yet unidentified mechanism that may involve changes in oxidative metabolism (Hunt and Idso 1999;Pawa and Ali 2006). BA also shows minimal potential for genotoxicity in bacteria and cultured mammalian cells (Moore and Expert Scientific Comittee 1997).…”
Section: Introductionmentioning
confidence: 99%
“…La vaginitis por C. krusei suele responder a azoles (excepto fluconazol) y al ácido bórico vaginal. En mujeres gestantes debe evitarse el uso de ácido bórico y anfotericina B [61].…”
Section: Etiología De Las Vulvovaginitis Por Candida (Vvc)unclassified